Malaria Strategic Plan towards Universal Access Policy - Malawi Government: Ministry of Health (Malawi Government, 2021)
The Ministry of Health (MoH) is pleased to present the new Malaria Strategic Plan for 2011-2015. Malaria continues to be the number one cause of morbidity and mortality in our country, with an estimated six million cases each year representing about 40% of the burden of illness in our health facilities. It is not selective, and all of us are at risk. However, malaria is a disease that can be prevented and treated effectively. This new Strategic Plan covering the next five years will provide the leadership and evidence-based direction needed to move confidently toward elimination of malaria as a public health threat in Malawi. The primary goal of this new plan will be the achievement of Universal Coverage in the prevention and treatment of malaria, reducing by half the 2010 levels of malaria morbidity and mortality in Malawi by the year 2015. This means every citizen of Malawi will be reached with all malaria interventions including care and effective cure. Over the period of the previous Malaria Strategic Plan (MSP) 2005-2010, the National Malaria Control Programme (NMCP) and its partners achieved significant improvements in addressing this dread disease, which has challenged not only the lives of our citizens but also the economic development of Malawi as a nation. As just one example, in the last two years, the government and its partners distributed 3.7 million long lasting insecticide treated nets (LLINs) for prevention. And in the next five years ahead, we will distribute millions more of these bed nets with the goal of having one net for every two people, in line with international best practices. In addition we will introduce the nationwide use of Rapid Diagnostic Tests so that every suspected case of malaria will be properly and promptly diagnosed and treated. In addition, malaria program management, drug procurement, distribution, monitoring and evaluation, and service delivery will be strengthened so that all malaria interventions will be provided in an integrated manner at all levels of the delivery system, including in communities and homes. We have a particular problem with malaria in Malawi, which is our belief about the nature of this disease. We are very worried about a death from AIDS or TB, but when it comes to malaria, we have become too accepting of its presence in our lives. Our perception of this disease must change to the point that everyone understands that malaria is not inevitable: it can be prevented and controlled if we all know how and when to take action. Accordingly, we will deliver widespread behavior change messages and education campaigns to empower communities to take charge of their own health by increasing use of Insecticide Treated Mosquito Nets (ITNs), speeding up the seeking of treatment at a facility for malarial symptoms, and encouraging a health-supportive and timely response to malaria at the community and household level. We have been paying a heavy price for malaria in illness, death, malnutrition, and losses of economic and social well-being. I therefore challenge all Malawians - parents, children, leaders, civil servants, health workers, all - to learn about this disease and take up the fight to prevent it and treat it when it occurs. We can defeat this disease only when we all play our parts.